Live Migration Performance Test on Linux-based Mail Server Service - Triansyah, Muhammad Bugi; Hendrawan, Ade Hendri; Afrianto, Yuggo; Kurniawan, Ridwan; Ritzkal, Ritzkal (Moneter: Jurnal Keuangan dan Perbankan, 2024)
The purpose of this study is to assess the performance of live migration of Linux-based email server services using Proxmox virtualization technology. The server usedemail that electronic mail serveris Squaremail, an open-source program running on the Ubuntu operating system.is Squaremail, an open-source program running on the Ubuntu operating system. The live migration process transfers Squaremail data and the Ubuntu operating system from one physical host to another without affecting running services.transfers Squaremail data and the Ubuntu operating system from one physical host to another without affecting running services.The migration is performed by utilizing Proxmox's live migration feature, utilizing which allows the transfer of virtual hosts without downtime. Proxmox's live migration feature, which allows the transfer of virtual hosts without downtime. migration process, the mail server was monitored to monitor the impact of live migration on service performance. study report on the results of downtime during the migration process without interruption and analyze the cost of using Proxmox to perform live migration on the Squaremail mail server.